Adjustable parameters-based control strategy for VSG-type grid forming converters considering grid strength - Hu, Xuekai; Li, Zifan; Shu, Zhipeng; Wang, Yaqin (Frontiers in Energy Research, 2024)
Introduction Grid-forming control has received increasing attention for being an effective solution to cope with low-inertia and weak damping systems. Owing to the basic characteristics of transient voltage regulation, inertia support and primary frequency regulation (PFR), virtual synchronous generator (VSG) is the most promising candidate of grid-forming control scheme. The damping characteristic plays a significant role in stabilizing when the system is disturbed. However, the traditional approaches for damping emulation pose a number of problems, such as the introduction of phase-locked loop (PLL) that may lead to stability issues, or the blurring of the functional distinction between damping characteristic and primary frequency regulation. Moreover, the grid strength affects the operational characteristics of the converters. Methods Based on the background of these issues, firstly, an effective transient damping power strategy is proposed in this paper. In contrast to conventional damping approaches, the proposed scheme provides a positive damping during transient period that suppresses the fluctuation of active power, and has no impact on the steady-state frequency droop characteristic. Ulteriorly, based on small-signal models and classical control theory, an parameters adjustment strategy for both active and reactive power control is proposed to considerably enhance the adaptability of the converter to the variations in grid strength. Results and Discussion The results obtained from PSCAD/EMTDC and hardware-in-the-loop (HIL) platform verify that proposed control strategy exhibits excellent transient damping effect, the decoupling characteristic between fixed damping coefficient and PFR coefficient, and performs well across a broad spectrum of grid strengths.